Academic Climate Reinforcement in An Effort of Establishing Start-ups Based on Student Business Determination - Abdul Aziz Bagis; Mahyudin Nasir (Department of Management, Faculty of Economics, Universitas Negeri Malang, 2020)
This study aims to confirm the role of students' business determination after completing entrepreneurship courses on productive behavior by reinforcing the academic climate experienced by students and ensuring the role of strong ideals and enthusiasm among students. This research primarily focused on students who have completed entrepreneurship courses in various study programs at the University of Mataram. The study involved students' attitudes in the form of determination that reflect the strong aspirations and enthusiasm of doing business and their influence on efforts to realize entrepreneurial intentions, in establishing novel, creative, innovative and innovative technology-based startup. It also measured how dare the students to take measurable risks. It comprehensively proved that student entrepreneurial behavior can be established on the basis of a strong desire to become entrepreneurs from the beginning of study, with the support of business knowledge and skills and strengthening the academic climate that creates psycho-social conditions such as academics.